Pemanfaatan Biji Kelor (Moringa oleifera) Sebagai Koagulan Dalam Menurunkan Kadar Fosfat (PO4) Pada Air Limbah Rumah Sakit - Hayat, A. M. Fadhil; Naim, St. Mu'tamirah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2020)
One alternative to solving the problem of wastewater treatment is to treat wastewater using Moringa seeds as a natural coagulant. Moringa seeds contain the bioactive compound rhamnosyloxy-benzil isothiocyanate, which can adsorb and neutralize mud and metal particles contained in suspension waste with dirt particles floating in water, so it has very potential to be used as a natural coagulant to clean water.This research was conducted to determine the method of wastewater treatment by using Moringa Oleifera Seeds for Phosphate (PO4) Content in Hospital Wastewater and calculating the difference in weight variations of Moringa oleifera seeds (1000, 1500, and 2000 mg / L) with deposition time (15 minutes). This type of research is quantitative research with true experimental research. The research design used was a randomized control-group pretest-posttest design.The results showed that in the range of observations made, the weight of Moringa seed powder as an effective coagulant was 2000 mg / L hospital wastewater with a deposition time of 15 minutes capable of removing phosphate levels by 28.77%.